The recycling potential of various local lignocellulosic residues for the cultivation of Pleurotus nebrodensis (Inzenga) Quél. - Akyüz, M.; Kırbağ, S. (MRF, 2026)
Various lignocellulosic waste products, generated from agricultural harvesting, present significant environmental challenges in terms of their use and disposal. The cultivation of mushrooms offers a cost−effective biotechnological method to recycle these lignocellulosic residues. This study aimed to assess the suitability of local lignocellulosic residues for the cultivation of P. nebrodensis, a relatively new species in mushroom cultivation. The study measured several parameters: spawn colonization periods (15.7−17.0 days), initiation of the first primordia (38.7−41.3 days), total harvest periods (77.3−83.3 days), and total yields (6.7−10.5 g/100 g) for P. nebrodensis grown on bean pods (BP), a mixture of bean pods and chickpea pods (BP−CP, 1:1), and a mixture of bean pods and wheat straw (BP−WS, 1:1). While there were no statistically significant differences in the first primordia initiation period, first harvest period, total harvest period, or second yield, significant differences were observed in spawn colonization period, first yield, second primordia initiation period, and total yields. These findings suggest that exploring less costly and more readily available alternative substrates, such as BP, CP, and WS wastes, could be advantageous for P. nebrodensis production. In conclusion, there is a need for further research on the cultivation of P. nebrodensis using various agricultural wastes, given its emerging status among cultivated mushrooms. © (2026), (MRF). All rights reserved.
Keywords: Agro−Wastes; Bioconversion Of Lignocellulosic Wastes; Edible Mushroom; Mushroom Cultivation; P. Nebrodensis